Effect of Particle Type on Cyclone Formation Inside a Solar Reactor - Chien, Min-Hsiu; Ozalp, Nesrin; Morrison, Gerald (Frontiers in Mechanical Engineering, 2016)
Solar reactors featuring a circulating cyclone flow pattern provide enhanced heat transfer and longer residence time increasing conversion efficiency. Cyclone flow also works in reducing particle deposition on solar reactor walls and exit which is particularly important issue in solar cracking reactors to avoid clogging. This paper focuses on the physics of cyclone formation inside a solar cracking reactor and experimentally analyzes the effect of particle entrainment on the flow pattern via two dimensional Particle Image Velocimetry (PIV). The cyclone flow structure in the reactor is reconstructed by capturing images from orientations perpendicular or parallel to the geometrical axis of the reactor. In order to conduct PIV measurements and to reconstruct the cyclone structure inside the solar reactor, the experiment was operated at room temperature with the flow configuration matching that of a solar reactor operating at high temperatures. Two types of seeding particles were tested, namely tri-ethylene glycol (TEG) and solid carbon. The effectiveness of the screening flow was evaluated by measuring the quantity of solid particles deposit on the reactor walls. The Stokes flow analysis of each particle species was performed and the cyclone vector fields generated by using different particles are compared.